Healthcare professionals’ well-being at work: A professional and organizational identity perspective - Nunes, F. G.; Oliveira, V. D. C. de.; Nascimento, G. do. (Journal of Health Organization and Management, 2024)
Purpose The purpose of this study is to test a model of healthcare professionals’ well-being seen as a consequence of a process of motivated professional identity construction, a variable that mediates the influence of the organizational identity (utilitarian or normative) and the perceived reputation of the profession on well-being. Design/methodology/approach Cross-sectional design, based on a survey of 384 healthcare professionals. Structural equation modeling with latent variables was used to test the model. Findings The data provide empirical evidence supporting the proposed model. We find that organizational identity (utilitarian and normative) and perceived professional reputation positively relate to professional identity, a variable that positively relates to well-being. Professional identity mediates the relationship between organizational identity (normative and utilitarian) and perceived professional reputation and well-being. Utilitarian organizational identity and perceived professional reputation are also directly related to well-being. Originality/value This research significantly departs from the current focus of explaining the well-being of healthcare professionals by resorting mainly to individual factors and introduces organizational and institutional determinants.